Penerapan Model Pembelajaran Kooperatif Tipe Team Games Tournament Berbantuan Media Jigsaw Puzzle Dalam Meningkatkan Hasil Belajar Peserta Didik - Yeni Oktaviani; Gugum Gumilar; Astri Srigustini (Pusat Riset dan Inovasi Nasional, 2026)
This study was motivated by the low learning outcomes of students in Economics. The low learning outcomes indicate the need for the implementation of a learning model that can increase students' engagement in the learning process. This study aimed to determine the effectiveness of the Team Games Tournament (TGT) cooperative learning model assisted by Jigsaw Puzzle media in improving students' learning outcomes compared to the conventional learning model using the lecture method.This study employed a quantitative approach with a quasi-experimental method and a non-equivalent control group design. The population consisted of all eleventh-grade students of SMAN 3 Tasikmalaya who took the Economics specialization, totaling 179 students. The research sample consisted of class XI-F.5 as the experimental class and class XI-F.12 as the control class, selected using a purposive sampling technique. Data were collected through learning outcome tests in the form of pretests and posttests. The obtained data were analyzed using SPSS Statistics 25.0 software.The results showed a difference in the improvement of learning outcomes between the experimental and control classes. Based on the N-Gain analysis, the experimental class obtained a score of 0.74, which was categorized as high, while the control class obtained a score of 0.53, which was categorized as moderate. Therefore, it can be concluded that the Team Games Tournament (TGT) cooperative learning model assisted by Jigsaw Puzzle media is more effective in improving students' learning outcomes in Economics among eleventh-grade students at SMAN 3 Tasikmalaya.